Evaluation of the effects of finish line type and width on the fracture strength of provisional crowns - Karaman, Tahir; Eser, Bekir; Altintas, Eyyup; Atala, Mustafa Hayati (Springer, 2021)
This study aimed to investigate the impacts of finish line type and width on the fracture resistance of provisional crowns, and to determine the suitable type of crown material to use for that purpose. Chamfer and rounded shoulder preparations were done with stainless steel master models with a width of 0.6 mm and 1.0 mm and a total convergence angle of 6 degrees. The provisional crowns were obtained using computer-aided design/computer-aided manufacturing (CAD/CAM) polymethyl methacrylate (PMMA) material in the mandibular left first molar. From the obtained molar tooth, a silicon mold was used to obtain the provisional crowns from the CAD/CAM PMMA, bis-acrylic resin, and self-curing composite materials. The lowest fracture strength was found in the bis-acrylic resin group made using the rounded shoulder preparation with a width of 0.6 mm (699 N). The highest fracture strength was found in the CAD/CAM PMMA group made using the rounded shoulder preparation with a width of 1 mm (1339 N). The fracture strength is higher for CAD/CAM PMMA than the other provisional crown materials; thus, it is recommended that this material be used in provisional crown restorations due to its other advantages.
Keywords: Provisional crown; Fracture strength; Finish line type; CAD; CAM PMMA; Bis-acrylic resin